Dimensi Pendidikan Dalam Ibadah Haji (Telaah Tentang Aspek Pendidikan: Tauhid, Etika, Moral, Sosial Yang Tersirat Dalam Pelaksanaan Ibadah Haji) - Muhaemin B Muhaemin (Jurnal Adabiyah: Humanities and Islamic Studies, 2013)
Muslims are obliged to do pilgrimage. This grand assembly not only infuses in them a spirit of joint cooperation and unity but also characterizes them as the members of one nation, one race and one family. The Haji is required to be the quintessence of virtue, peace, self-control and self-sacrifice during the Hajj days. He must eschew querrelling with and troubling others and even killing a animal. Even games of the land are unlawful for him. How explicit and clear-cut this command is that there should be no expression of carnal desires directly or metaphorically. In the state of "Ehraam" lawful hobbies like games of the land are forbidden let alone sins and disobedience. Argument, altercation and scuffle that generally take place on such occasions are also forbidden even rebuking one's own servant. This standard of inward and outward purification set by Islaam for worship is so lofty that it has not only impressed and won over the hearts of the believers but also the disbelievers.